Determining significant parameters on health and well-being of building occupants towards re-engineered inclusive environment - S. N. Kamaruzzaman,; A. Razali,; E. M. Ahmad Zawawi,; Riley, Michael L. (Penerbit Universiti Kebangsaan Malaysia, 2018)
People spend over 90% of their time in the buildings. A building is a place where people are spending more time doing activities, thus an inclusive environment of the buildings is very important to ensure that people are having a healthy life. An inclusive environment is important for the well-being of building occupants. Indoor environmental quality is one of the essential elements in creating an inclusive environment in which a poor quality of indoor environment affects the health of the occupants both physically and mentally, their performance, productivity, comfort, satisfaction, and well-being. Even though people are towards creating an inclusive environment but it is a limited study on the parameters of the inclusive environment. Thus, this paper is to study the parameters of the inclusive environment by focused on the element of the indoor environmental quality for building occupants based on literature reviews of articles between the year 2006 and 2016. Based on the content analysis, it has been discovered that there are various parameters of an inclusive environment which are visual comfort, thermal comfort, acoustic comfort, indoor air quality, buildings factors, occupants’ factors, and climate condition factors. The parameters can be very useful as guidelines and development of policy in providing inclusive environment for the healthy lifestyle of building occupants.